Pesticides and their metabolites in selected Italian groundwater and surface water used for drinking - Luca Fava; Maria Antonietta Orrù; Simona Scardala; Elena Alonzo; Maristella Fardella; Caterina Strumia; Angiolo Martinelli; Sabrina Finocchiaro; Massimo Previtera; Alessandro Franchi; Piergiuseppe Calà; Mauro Dovis; et al. (Istituto Superiore di Sanità, 2010)
The control of groundwater and surface water quality in relation to the presence of pesticides and their metabolites is a rather complicated task. National and local authorities with the responsibility to guarantee an adequate quality of water cannot rely on international guidelines for monitoring activities. In a national project, forty-three pesticides and pesticide metabolites were selected on the basis of sale, monitoring and physical-chemical data, and investigated from some of the main Italian agricultural areas, susceptible to pesticide contamination. Twelve compounds were found in the tested water samples at levels exceeding the 0.1 µg/L European Union (EU) limit for drinking water (European Directive 98/83/EC). Maximum levels up to 0.62 were determined. Several water samples were characterized by the simultaneous occurrence of pesticides and their metabolites (up to ten). In some samples, the total concentration of pesticides and their metabolites was higher than the EU limit of 0.5 µg/L. Total triazine concentrations up to 1.02 µg/L were found. In all the cases the highest concentrations were well below the respective guideline values defined by the World Health Organization (WHO) for drinking water quality.